2021
DOI: 10.1038/s42255-021-00479-4
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological inhibition of fatty acid synthesis blocks SARS-CoV-2 replication

Abstract: Caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), COVID-19 is a virus-induced inflammatory disease of the airways and lungs that leads to severe multi-organ damage and death. Here we show that cellular lipid synthesis is required for SARS-CoV-2 replication and offers an opportunity for pharmacological intervention. Screening a short-hairpin RNA sublibrary that targets metabolic genes, we identified genes that either inhibit or promote SARS-CoV-2 viral infection, including two key candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 48 publications
3
80
0
Order By: Relevance
“…FASN (Fatty Acid Synthase) is one of the rate-limiting enzymes in fatty acid synthesis and the key enzyme in the synthesis of palmitate. Knockdown of FASN in cell lines resulted in lower SARS-CoV-2 infection and lower quantity of viral RNA [ 80 ]. The same study also showed that inhibiting fatty acid synthesis by drugs, such as orlistat, lowered viral levels in the lung and increased survival in a mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…FASN (Fatty Acid Synthase) is one of the rate-limiting enzymes in fatty acid synthesis and the key enzyme in the synthesis of palmitate. Knockdown of FASN in cell lines resulted in lower SARS-CoV-2 infection and lower quantity of viral RNA [ 80 ]. The same study also showed that inhibiting fatty acid synthesis by drugs, such as orlistat, lowered viral levels in the lung and increased survival in a mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…1D ). Since pharmacological inhibition of fatty acid synthesis in SARS-CoV-2 infected hPSC-AO, HEK293T-hACE2 cells and K18-hACE2 mice inhibits viral replication ( 14, 40 ), induction of fatty acid biosynthesis must be required for viral replication, perhaps for the formation of the viral double membrane assembly structures ( 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that high level of ACSL1 expression induced by coronavirus infection can directly enhance inflammatory phenotypes of infected macrophages via a remodeling of lipid metabolism. Although inhibiting fatty acid synthesis was reported to block SARS-CoV-2 replication [69], it is still unclear how coronavirus infection alters the cellular lipid metabolism, especially the involvement of acyl-CoA synthetase long-chain family members. As an acyl-CoA synthetase long-chain family member, ACSL1 was recently identified to promote α-eleostearic acid triggered ferroptosis.…”
Section: Discussionmentioning
confidence: 99%